Neural network-based MRAC control of dynamic nonlinear systems - Debbache, Ghania; Bennia, Abdelhak; Goléa, Noureddine (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents direct model reference adaptive control for a class of nonlinear systems with unknown nonlinearities. The model following conditions are assured by using adaptive neural networks as the nonlinear state feedback controller. Both full state information and observer-based schemes are investigated.
Keywords: neural networks; reference model; nonlinear systems; adaptive control; observers; stability; LMI